Quality assessment of frozen fruit pulps marketed in the Carajás-PA Region (Research, Society and Development, 2020)
The fruit pulp market is a promising and profitable business within the food industry, factors such as convenience and fruit varieties in Brazil made this type of product highly appreciated by consumers. The present study aimed to evaluate the physical-chemical and microbiological characteristics of fruit pulps marketed in the Carajás-PA region, and to compare with the current legislation. To this end, five flavors (pineapple, acerola, cajá, cupuaçu and guava) from four fruit pulp brands (A, B, C and D) were analyzed for pH, total soluble solids (ºBrix), total titratable acidity and total solids. The microbiological analyzes carried out on the pulps of different brands were Coliforms at 45 °C and Salmonella sp. The results obtained for the same flavor, from different brands, were subjected to analysis of variance and comparison of means by the Tukey test at 5% significance. The results verified in the fruit pulps of the different brands, indicated the absence of microorganisms. The B brand of the different pulps was the one that best met the required standards; and the main parameters in disagreement with the legislation are the content of total soluble solids (ºBrix) and total solids, which suggests the adequacy of the industries in relation to the processing and quality control of the pulps sold in the Region of Carajás-PA.